2017
DOI: 10.48550/arxiv.1712.08940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Studying the Impact of Managers on Password Strength and Reuse

Abstract: Despite their well-known security problems, passwords are still the incumbent authentication method for virtually all online services. To remedy the situation, end-users are very often referred to password managers as a solution to the password reuse and password weakness problems. However, to date the actual impact of password managers on password security and reuse has not been studied systematically.In this paper, we provide the first large-scale study of the password managers' influence on users' real-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Lyastani et al [21] argued that passwords are still the default authentication scheme for most online services and that no alternative scheme has been found as a replacement for passwords. They concluded that password managers help users with the strength and uniqueness of their passwords.…”
Section: Discussionmentioning
confidence: 99%
“…Lyastani et al [21] argued that passwords are still the default authentication scheme for most online services and that no alternative scheme has been found as a replacement for passwords. They concluded that password managers help users with the strength and uniqueness of their passwords.…”
Section: Discussionmentioning
confidence: 99%